Detection of mouse mast cell-associated protease mRNA. Heparinase treatment greatly improves RT-PCR of tissues containing mast cell heparin. - Tsai, M. (1995)
The reverse transcriptase polymerase chain reaction (RT-PCR) procedure is markedly inhibited in specimens of blood that contain commercial heparin as an anticoagulant or in cell preparations containing rat or mouse peritoneal mast cells. However, it was not known whether the levels of endogenous, mast cell-associated heparin that are present in some mammalian tissues are sufficient to interfere with the use of RT-PCR in these settings. We show that RT-PCR detects little or no mRNA transcripts for either mast cell-associated products, such as mouse mast cell-associated protease-2 or -4 (MMCP-2 or MMCP-4) or mast cell carboxypeptidase A, or for mast cell-nonspecific products, such as glyceraldehyde 3-phosphate dehydrogenase, in routinely prepared specimens of cells or tissues that include populations of heparin-containing mast cells. However, signals for mast cell-associated or mast cell-nonspecific transcripts can be readily detected in such specimens if they are treated with heparinase before RT-PCR. RT-PCR after heparinase treatment appears to represent an extremely sensitive method for detecting mast cell-associated transcripts in tissue specimens, permitting the identification of transcripts for mast cell-specific proteases in the skin of genetically mast cell-deficient WBB6F1-W/WV mice, a tissue that contains few or no mast cells according to histological analysis.